Desain Ulang Troli Pengering Mie dengan Metode Antropometri - Joy Christian; I Gusti Ngurah Priambadi; Desak Ayu Sista Dewi; I Wayan Bandem Adnyana; I Gusti Agung Kade Suriadi; Ni Luh Putu Lilis Sinta Setiawati (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
Comfortable work can make it easier for employees to work. Good working processes can improve company performance and employees will work comfortably in their jobs. The noodle dryer currently used in industry X has employees complaining of pain in their body parts. Based on data collection in the Nordic Body Map form, this complaint arose due to the inappropriate height of the noodle hangers on the trolley. This research aims to reduce the level of complaints from workers by redesigning the noodle drying trolley in Industry X. This research uses an anthropometric approach to redesign and obtain an ergonomic trolley height. The trolley redesign is based on calculating percentile data to obtain a more ergonomic trolley height. After calculating the proper height of the trolley using the worker’s body height, the result of the ergonomic trolley height is 163.4 cm. These results are then applied to the new trolley height, until the height of the trolley adjusts to the body height of the workers, thereby reducing the level of worker complaints. The results obtained in this study were a reduction in complaints from 26 to 4 complaints (reduction by 84.61%).